The factors that influence youth consumption of junk food / Nur Shahirah Shamsol and Nur Nadia Maisarah Mohd Fisol - Shamsol, Nur Shahirah; Mohd Fisol, Nur Nadia Maisarah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The rapid development of technology in the food industry has increased the number of junk food products consisting of various types and flavors. Moreover, the number of junk food consumers among the youth is also increasing along with the food industry's development. Hence, this research is conducted to determine the factors that influence youth intake and junk food consumption. This quantitative study was conducted by distributing a self-administered questionnaire involving 365 respondents from Universiti Teknologi MARA Cawangan Pulau Pinang Kampus Permatang Pauh and analyzed using Statistical Package for the Social Sciences (SPSS) version 21. The results showed a positive relationship between food trends, parental control, and friends' influence on junk food consumption.